GC/MS Characterization of The Non-Polar Phytochemical Constituents from Leaves of Hydrangea macrophylla Cultivated in Baghdad-Iraq - Fadhil, Nawras Khairi (Tikrit Journal of Pharmaceutical Sciences, 2024)
Background: Hydrangea macrophylla is a medicinal plant with a long history of use in traditional medicine, particularly for its supposed diuretic and antioxidant effects. Objective: The purpose of this study was to analyze the phytochemical contents and identify the key non-polar active chemicals in the leaves of Hydrangea macrophylla, also known as French Hydrangea, cultivated in Baghdad, Iraq. Methods: Non-polar compounds were extracted using Soxhlet as hot hexane extraction and subsequently analyzed by Gas Chromatography-Mass Spectrometry (GC-MS). Results: Preliminary phytochemical screening revealed the presence of terpenoids, saponins, and flavonoids in the methanol extract of the leaves. The GC-MS analysis of the hexane extract identified seven major peaks corresponding to terpene-based compounds, with the primary constituents being squalene (4.43%), heneicosane (2.7%), heptacosane (2.1%), and hexacosane (2.7%). These compounds are known for their diverse pharmacological activities, including antioxidant, anti-inflammatory, and antimicrobial effects. Conclusion: There were relatively numerous of phytochemicals present in the hexane extract from leaves collected before flowering. These findings highlighted the importance of environmental factors, such as soil conditions and harvest timing, on the chemical composition of the plant. Further studies are recommended to explore the plant's polar constituents and investigate their therapeutic applications.